Adequacy of biopsy samples for epidermal growth factor receptor (EGFR) molecular testing in lung adenocarcinoma - Tegeltija, Dragana; Lovrenski, Aleksandra; Vasiljević, Tijana; Andrejić-Višnjić, Bojana (Vojnosanitetski pregled, 2021)
Background/Aim. Adenocarcinoma of the lung is the most common histological type of lung cancer. The most reliable method in detecting epidermal growth factor receptor (EGFR) mutations is real-time polymerase chain reaction (PCR). It is recommended to sample three to five biopsy samples with a minimum of 200–400 preserved tumor cells. We analyzed the suitability of biopsy samples for EGFR molecular testing in lung adenocarcinoma. Methods. This retrospective analysis included 60 patients diagnosed with lung adenocarcinoma at the Institute for Pulmonary Diseases in Sremska Kamenica, Serbia from 2010 to 2015. Biopsy samples were obtained using transbronchial, bronchoscopic, or catheter biopsy procedures. All cases included the identification of morphometric parameters, the concentration of isolated DNA, and EGFR mutations. The proportion of tumors in biopsy samples was assessed in histological sections using computer-aided morphometry. Results. Biopsy samples were most commonly obtained by transbronchial biopsy (63%). In 35% of cases, there was either one or two biopsy samples. More than 10% of tumor cells were found in 68% of cases, while the majority of cases (33%) had between 200 and 500 tumor cells and only 8% of cases had between 20 and 50 tumor cells. The average concentration of DNA in all analyzed samples was 5.81 ng/µL and was significantly lower in samples provided by catheter biopsy. Only two cases with mutations were detected, and there was no statistically significant difference between the concentrations of isolated DNA in the wild type and mutated EGFR adenocarcinoma. Invalid results were found in 10% of cases. Conclusion. Biopsy samples are suitable for EGFR molecular testing in lung adenocarcinoma.